Building democracy and international governance - Guess, George M. (New York Routledge, 2019)
From diaries and letters to surveys and interview transcripts, documents are a cornerstone of social science research. This book guides you through the documentary research process, from choosing the best research design, through data collection and analysis, to publishing and sharing research findings. Using extensive case studies and examples, it situates documentary research within a current context and empowers you to use this method to meet new challenges like digital research and big data head on. In a jargon-free style perfect for beginner researchers, this book helps you to : · Interrogate documentary material in meaningful ways -- · Choose the best research design for your project, from literature reviews to policy research, -- · Understand a range of approaches, including quantitative, qualitative and mixed methods. Accessible, clear and focused, this book gives you the tools to conduct your own documentary research and celebrates the importance of documentary analysis across the social sciences.
1. Introduction : the need for effective government. -- 2. Challenges to effective government : ethnic-nationalism, populist nationalism and weak state institutions. -- 3. Wealthier state populist nationalism. -- 4. Macroeconomic instability. -- 5. Inability of both wealthy and poor countries to reduce regional inequalities. -- 6. Governing structures. -- 7. Response to governance challenges : the problem of aid design and implementation. 8. Aid as stimulus for democracy and governmental effectiveness. -- 9. Targeting aid to threats against improved governmental effectiveness. -- 10. Specific problems with design and implementation of aid. -- 11. Summary and conclusions. -- Appendix : managing development projects in high risk environments : the case of Pakistan / George M. Guess and Dennis Desantis. -- References. -- Index.
Includes bibliographical references and index.
Keywords: Democratization; Democratization -- International cooperation; Government accountability; Organizational effectiveness; Democracy -- Economic aspects; Economic development -- Political aspects